Upaya Peningkatkan Collaboration Skills Peserta Didik SD Melalui Penerapan Project Based Learning (PjBL) - Hendrawati, Ririn; Winanto, Adi; Kristanti, Hana Septina (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to improve the collaboration skills of third-grade students at SD N Ledok 01 Salatiga by applying the Project Based Learning (PjBL) Model. The type of this research is a collaborative classroom action research (PTKK). The subject of this research were 26 third-grade students. This study uses a spiral spin model design developed by Kemmis and Mc Taggart. This research was conducted in 2 cycles. Each cycle consists of 3 stages, namely the planning stage, the implementation and observation stage, also the reflection stage. This research is successful if it achieves success indicators<80%. Data collection techniques are in the form of observation, interviews and documentation. Data analysis used is descriptive qualitative and quantitative. The results showed that the Project Based Learning (PjBL) Model can increase collaboration skills occurring in each cycle which has been shown that students can interact with group mates while doing assignments, which is shown in the pre-cycle of 0%, cycle I of 54%, and cycle II by 81%. Mutual assistance has increased as shown in the pre-cycle of 0%, cycle I of 62%, and cycle II of 85%. Student’s ability to be responsible increased as shown in the pre-cycle of 0%, cycle I of 58%, and cycle II of 85%.